2009
DOI: 10.1080/08982100802673940
|View full text |Cite
|
Sign up to set email alerts
|

The encapsulation and release of guanosine from PEGylated liposomes

Abstract: The encapsulation and release kinetics of guanosine from liposomes and polyethylene glycol (PEG)-modified liposomes are reported. Specifically, the influence of PEG chain length, PEGylation level, lipid type, drug-loading level, temperature, and solution conditions (i.e., salt and pH effects) on the rate and mechanism for release have been determined. Increasing PEGylation significantly reduced the guanosine release kinetics; this is more significant for greater molecular weight PEG and is correlated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…Moreover, the PEGylated liposomes had higher retention capability than conventional liposomes therefore this is another reason for greater cytotoxicity of conventional against PEGylated liposomes. This greater retention capability of PEGylated liposomes has been reported by other researchers …”
Section: Discussionsupporting
confidence: 60%
“…Moreover, the PEGylated liposomes had higher retention capability than conventional liposomes therefore this is another reason for greater cytotoxicity of conventional against PEGylated liposomes. This greater retention capability of PEGylated liposomes has been reported by other researchers …”
Section: Discussionsupporting
confidence: 60%
“…In addition to the steric stabilization, PEG-phospholipids also influence the liposome permeability and the rate and mechanism of drug release [52]. For instance, the increase in DMPE-PEG level in the liposomes was found to significantly reduce the release rate constant of encapsulated guanosine [53]. The investigators also found that the mechanism of guanosine release changed from diffusion-controlled to interfacial-controlled, as the amount of PEG-phospholipid in the bilayer was increased, and the magnitude of the effect was directly dependent on the MW of PEG [53].…”
Section: Poly(ethylene Glycol)-linked-lipids (Peg-lipids)mentioning
confidence: 99%
“…This formulation achieved an encapsulation efficiency of ~50%. Only 3.3 mol% of PEG 2000 was used in this study as a higher PEG content is known to reduce adsorption of liposomes onto cells [41]. …”
Section: Discussionmentioning
confidence: 99%